(untitled) (Research, Society and Development, 2020)
The present study considers the literary production from the American author Alice Walker; whose representations bring questions that submerge from human social practices. The aim in this paper is to express the possible reflections that literature promotes from the text The right to life: What the white man said to the black woman?, which is written and pronounced by Walker. Methodologically, the analysis is organized based on this narrative and it is built from the scope of theoretical studies, especially from those that consider the literature written by black women in the twentieth century and that are linked to sociocultural criticism. The results show that the literature, in addition to being the space and time for reflection, allows that the tensions between the oppressor’s discourses and those who suffer domination can be identified. Walker confronts history, denounces and questions the dominator’s responsibility while she shares her literary art in the collectively way.